Correlation of Nasal Fluid Biomarkers and Symptoms in Patients with Persistent Allergic Rhinitis. (June 2020) - Kim, Su Il; Kwon, Oh Eun; Park, Jung Min; Doo, Jeon Gang; Kim, Seok Hyun; Jung, Hae Rim; Min, Jin Young; Kim, Sung Wan; Lee, Young Chan; Eun, Young-Gyu
Objectives: This study investigated whether the biomarkers present in nasal fluid reflect the severity of symptoms in patients with persistent allergic rhinitis (PAR). Methods: We enrolled 29 PAR patients complaining of nasal symptoms and testing positive to skin prick test. Patients' total nasal symptom score (TNSS) was measured and their nasal lavage fluid (NALF) was collected. The levels of biomarkers including Clara cell protein 16 (CC16), tryptase, and interleukin 5 (IL-5) in NALF were determined via enzyme-linked immunosorbent assay (ELISA). Results: PAR patients were classified into persistent mild and persistent moderate-to-severe groups according to the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines. The CC16 alone was significantly negatively correlated with TNSS ( P  < .05). Further, the CC16 level was significantly lower in persistent moderate-to-severe group than persistent mild group of patients ( P  < .05). Conclusions: The levels of CC16 alone among several NALF biomarkers showed an inverse correlation with symptoms of PAR patients.